The Poetic Phrase - Montealegre, Viviana (Disertaciones, 2019)
In this brief reflection we will center our atention on two aspects of the poetic phrase, the first is rhythm, the second, metaphor. We will refer to rhythm as image, musicality and sens trascending metrics, and methapor as a figure of thinking and a vehicle to get into a new world’s perception. The analisys of these two elements offers a hermeneutic approach to the poem as becoming.